2018
DOI: 10.1186/s40425-018-0352-8
|View full text |Cite
|
Sign up to set email alerts
|

In-field and abscopal response after short-course radiation therapy in patients with metastatic Merkel cell carcinoma progressing on PD-1 checkpoint blockade: a case series

Abstract: BackgroundPatients with metastatic Merkel cell carcinoma (mMCC) who experience disease progression on immunotherapy have limited additional standard options. Given evidence of synergism between radiation therapy (RT) and immunotherapy, two patients progressing on PD-1 inhibition were referred for short-course RT.Case presentationTwo patients were found to have progressive mMCC on PD-1 inhibitor therapy and were treated with single-fraction palliative RT. Both patients were observed to have local control at irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 22 publications
0
33
0
2
Order By: Relevance
“…Despite the lower BED of SFRT, the similar local control may be explained by emerging data demonstrating that higher dose per fraction may potentiate a greater immune-mediated effect compared with conventionally fractionated RT. 17 , 18 , 19 This is relevant given MCC is a highly immunogenic malignancy. 20 Ongoing work will refine the ideal patient population for postoperative SFRT.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lower BED of SFRT, the similar local control may be explained by emerging data demonstrating that higher dose per fraction may potentiate a greater immune-mediated effect compared with conventionally fractionated RT. 17 , 18 , 19 This is relevant given MCC is a highly immunogenic malignancy. 20 Ongoing work will refine the ideal patient population for postoperative SFRT.…”
Section: Discussionmentioning
confidence: 99%
“…Before the advent of immunotherapy, RT was mainly seen as a palliative measure. The search to overcome refractory disease has brought with it a rise in reports on the abscopal effect in metastatic MCC [24,46]. RT modulates the tumour immunoediting process by various and partly unidentified mechanisms, such as altering tumour cell antigen presentation, increasing the infiltration of regulatory T-cells in the tumour microenvironment and staging of T-cell exhaustion with debulking the tumour mass [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that RT effects are achieved at least partially through immune system response. RT does not only affect the targeted tumour areas, but can have a beneficial abscopal effect on malignant growth elsewhere [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, RT is often used as an adjuvant to surgery, as well as it is an alternative to lymph node dissection 30. Palliative RT is used in inoperable disease,30 and single-fraction palliative RT has shown benefit in two patients who have progressed on immune checkpoint inhibitors, leading to long-term abscopal responses in non-irradiated sites 31…”
Section: Discussionmentioning
confidence: 99%